Analisis pemasaran lobster mutiara (Panulirus ornatus) di Kabupaten Lombok Timur - Ahmadi, Fadlika; Husni, Syarif; Nursan, Muhammad (Universitas Muhammadiyah Mataram, 2022)
East Lombok Regency is one of the priority areas in the development of pearl lobster, so it has received government attention with the construction of a lobster village in the Jukung Bay Area as the foundation for the construction of a lobster estate in the region. One of the important goals of this development is the creation of information and market access that is open to cultivators so that they no longer depend on the price of pearl lobsters from suppliers. The concept of an efficient supply chain needs to be carried out to determine the distribution of pearl lobster commodities from producers to consumers which can result in satisfaction between both parties. This study aims to determine the marketing channels of pearl lobster in East Lombok Regency and analyze the efficiency of these marketing channels. The method used in this research is descriptive quantitative and qualitative methods with data collection techniques using interviews. Pearl lobster marketing analysis was carried out using descriptive methods while marketing efficiency analysis was carried out using producer shares and marketing margins. The results show that there are two kinds of pearl lobster marketing channels in East Lombok Regency, namely marketing channel I with the scheme of cultivators collectors wholesalers (exporters)/consumers and marketing channel II with cultivator consumer schemes. The value of the producer's share in marketing channel 1 is 89.49% with a marketing margin of Rp. 82,000 while the share value of producers in marketing channel II is 100% so the marketing of pearl lobster in East Lombok Regency is efficient because it has a producer share value of ≥60%. Based on these results, it can be concluded that there are two marketing channels for pearl lobster in East Lombok Regency, where these marketing channels are classified as efficient.